Positioning Austria in the Global Economy: Value Added Trade, International Production Sharing and Global Linkages - Robert Stehrer; Roman Stöllinger (FIW - Research Centre International Economics, 2013)
This study investigates Austria's positions in international production sharing and global value chains exploiting the recently available Global Input-Output Database (WIOD). Researchers and policy-makers become increasingly aware of the fact that production processes are more and more organised internationally, which implies that indicators based e.g. on gross export values become less meaningful as part of this value is made of imported intermediates. As such, statistics and indicators based on a value added rather than gross trade basis and emphasis on the actual (domestic) value added creation due to exports are needed for policy-makers and researchers to draw a more accurate picture of the link between trade and value added creation and the implications thereof. Making use of indicators for measuring different aspects of complex production relations established in the literature such as the degree of vertical specialisation, value added trade and global value chain income, we find that Austria has intensified its participation in international production sharing since 1995 as evidenced, e.g., by the substantial increase in its vertical specialisation index. Tight supplier-customer relationships, above all in medium-high- and high-technology-intensive manufacturing industries, with Germany and increasingly with the neighbouring CEEC economies have contributed strongly to this development. However, international production sharing is also inextricably linked to employment sharing', meaning that in the presence of vertical specialisation not all jobs related to Austrian exports are also located in Austria. In fact, if based on the individual countries' labour productivities, Austrian exports embody more foreign than domestic jobs due to significantly lower productivity levels in some of the partner countries. Nevertheless, the development of Austrian exports has been very dynamic over the past decade as manifested for example in a trade surplus since the early 2000s. A counterfactual exercise that compares the actual amount of domestic jobs embodied in Austrian exports with the hypothetical amount of jobs that would be needed to produce Austria's imports domestically suggests that foreign trade has a positive employment impact in Austria amounting to some 90,000 jobs in 2009 - a result that is closely linked to Austria's trade balance surplus. The strong export performance of Austria is also revealed by the rising share in total EU value added exports which exceeded 3% in 2011, though this is sometimes masked by the fact that the share in global value added exports declined slightly between 1995 and 2011 as a result of new important players in the arena of international trade, above all China. Finally, analysing the trade slump of the year 2009 we find that re-shoring' activities of Austrian firms as well as the so-called composition effect' contributed to the crisis-related decline of Austrian exports.
Keywords: F14; F15; F63; O52; 330; production fragmentation; value added trade; internationalisation